Knowledge and practice of iodine salt utilization and associated factors among pregnant women attending antenatal care in public health facilities in Addis Ababa, Ethiopia - Ejigu Girma; Habtamu Molla Ayele; Elzabeth Seyoum; Getachew Weldeyohannes (Frontiers in Nutrition)
BackgroundGlobally, iodized salt deficiency affects more than 2.2 billion people, and the effect is severe in pregnant women. Several factors contribute to the insufficient utilization of iodized salt in the population. Knowledge and practice of iodized salt utilization contribute to improving the utilization of iodized salt among pregnant mothers.ObjectiveThis study aimed to assess the knowledge and practice of iodized salt utilization and its associated factors among pregnant women attending antenatal care at public health facilities in Addis Ababa, Ethiopia.MethodA facility-based cross-sectional study was conducted in the primary public health centers of selected sub-cities in Addis Ababa from 6 May to 20 July 2022, using interviewer-administered structured questionnaires. The total sample size was 472 participants. Data entry was performed using Epi Data version 3.1 and imported to SPSS version 23 to perform various analyses. Bivariable logistic regression analysis was performed to identify candidate variables with a p-value <0.25, and then multinomial logistic regression analysis was conducted to determine the level and factors associated with iodized salt utilization. In the multivariable model, adjusted odds ratios, together with their corresponding 95% CI, were calculated to assess the strength of association and to declare statistical significance at a p-value <0.05.ResultsAmong the 463 respondents, 190 (41.1%) had good knowledge of iodized salt, whereas 270 (58.3%) had good practices for iodized salt utilization. Occupation, average monthly income, and the number of pregnancies were significantly associated with knowledge of iodized salt utilization. Educational level, average monthly income, and the number of ANC visits were significantly associated with good practices for iodized salt utilization.Conclusion and recommendationsBased on the findings of this study, it can be concluded that women attending antenatal care have low levels of iodized salt knowledge and practice in the study area. Nutritional interventions, such as nutrition education, should be provided to the community, particularly for pregnant mothers.